Surgical treatment of asymptomatic epithelioid hemangioendothelioma originating from the superior vena cava: A case report. Issue 16 (April 2020) - Lee, Seok Soo; Lee, Jang Hoon
Abstract: Rationale: Epithelioid hemangioendothelioma is a rare endothelial tumor with a low-grade malignancy. This tumor can be treated with complete resection. Patient concerns: A 20-year-old Korean man visited our hospital due to an abnormal finding on standing chest PA X-ray. He did not have any past medical history. Diagnosis: Chest computed tomography shows a well-defined, oval-shaped tumor invading the brachiocephalic vein and superior vena cava. A malignant tumor of vascular origin was diagnosed by a percutaneous needle biopsy. Interventions: We performed en-bloc resection including the great vessels for complete resection of the tumor. Histologic evaluation confirmed the lesion to be a hemangioendothelioma and the surgical margins were free from tumor invasion. Outcomes: Fourteen days later, the patient was discharged without any complication. Thirty months after surgery, recurrences, or metastasis were not detected. Lessons: Epithelioid hemangioendothelioma is a rare malignant endothelial tumor in the central vein. Surgery is the treatment of choice and shows good results. We introduce and appropriate surgical method to ensure successful treatment for rare disease.